Antitesis Peraturan dan Problematika Penerapan Cyber Notary di Indonesia - Aulia, Ichsan; Roisah, Kholis (Program Studi Magister Kenotariatan, Fakultas Hukum, Universitas Diponegoro, 2026)
ABSTRACTThe enactment of Law Number 2 of 2014, which amends Law Number 30 of 2004 concerning the Office of Notary, aims to support the implementation of the Cyber Notary concept in Indonesia’s legal system. However, its implementation still faces various legal obstacles, resulting in inconsistencies within the regulatory framework. This study aims to analyze regulatory disharmony and challenges in the implementation of Cyber Notary in Indonesia. This research employs a normative juridical method with an analytical approach to legal theories and a comparative study of relevant legislation. The findings indicate that the implementation of Cyber Notary has not been effective due to the lack of regulatory alignment. Consequently, the digitalization process of notarial services in Indonesia encounters significant obstacles, preventing the optimal realization of technology-based notarial services.Keywords: Cyber Notary; Indonesia; Regulatory Contradictions.ABSTRAKUndang-Undang Nomor 2 Tahun 2014 yang mengubah Undang-Undang Nomor 30 Tahun 2004 tentang Jabatan Notaris telah diberlakukan untuk mendukung konsep Cyber Notary dalam hukum Indonesia. Namun, implementasinya masih menghadapi kendala hukum yang menciptakan ketidaksesuaian dalam sistem perundang-undangan. Penelitian ini bertujuan untuk menganalisis ketidaksesuaian regulasi serta problematika dalam penerapan Cyber Notary di Indonesia. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan analisis terhadap teori hukum serta perbandingan undang-undang terkait. Hasil penelitian menunjukkan bahwa penerapan Cyber Notary belum dapat berjalan secara efektif karena adanya disharmoni regulasi. Akibatnya, proses digitalisasi layanan Notaris di Indonesia masih terhambat, sehingga transformasi menuju layanan notaris berbasis teknologi menghadapi tantangan yang signifikan.Kata Kunci: Cyber Notary; Indonesia; Antitesis Peraturan.